2016
DOI: 10.1016/j.clinph.2016.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Discovering EEG resting state alterations of semantic dementia

Abstract: HighlightsResults: Topographical differences between the groups were found in microstate classes B and C, while microstate classes A and D were comparable. The data showed that the semantic dementia group had a peculiar microstate E, but the commonly found microstate C was lacking. Furthermore, the presence of microstate E was significantly correlated with lower MMSE and language scores. Conclusion: Alterations in resting EEG can be found in semantic dementia. Topographical shifts in microstate C might be rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 45 publications
5
32
0
Order By: Relevance
“…Previous works showed that a modification of microstate topography and metrics is possible by cognitive manipulation 19 . Moreover, altered topographies and metrics have been found in the acute phase of the stroke as a consequence of a mono-hemispheric lesion 18 , as well as in neurodegenerative or psychiatric diseases 20 . Our study adds the evidence that the topography and metrics of microstates can be modified also by active inhibition by means of magnetic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works showed that a modification of microstate topography and metrics is possible by cognitive manipulation 19 . Moreover, altered topographies and metrics have been found in the acute phase of the stroke as a consequence of a mono-hemispheric lesion 18 , as well as in neurodegenerative or psychiatric diseases 20 . Our study adds the evidence that the topography and metrics of microstates can be modified also by active inhibition by means of magnetic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of electric microstates of the brain comes from the observation that the topography of the electric field recorded by EEG over the scalp does not fluctuate randomly, but is instead comprised of short periods of stability (Lehmann 1971 ). Four canonical microstates (Koenig et al 2002a , b ), conventionally labelled A, B, C and D, have been shown to be consistent across recording sessions (Khanna et al 2014 ) and have been repeatedly confirmed in a wide range of health conditions and cognitive tasks across multiple studies (Britz et al 2010 ; Brodbeck et al 2012a , b ; Grieder et al 2016 ; Katayama et al 2007 ; Kikuchi et al 2011 ; Koenig et al 1999 ; Kuhn et al 2015 ; Milz et al 2015 ; Nishida et al 2013 ; Pascual-Marqui et al 2014 ; Schlegel et al 2012 ; Strelets et al 2003 ; Tomescu et al 2014a , b ; Van de Ville et al 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneous fMRI-EEG studies as well as EEG source imaging studies suggest that these microstate classes correspond to the activity of previously identified networks for phonological processing, the visual network, the saliency network, and attention network, respectively ( Britz et al, 2010 ; Custo et al, 2017 ). Alterations in the expression of these microstates have been observed in a variety of neuropsychiatric conditions including depression ( Atluri et al, 2017 ), Alzheimer’s disease ( Dierks et al, 1997 ; Strik et al, 1997 ; Nishida et al, 2013 ), frontotemporal dementia ( Strik et al, 1997 ; Nishida et al, 2013 ; Grieder et al, 2016 ), stroke ( Zappasodi et al, 2017 ), and schizophrenia ( Merrin et al, 1990 ; Stevens et al, 1997 ; Strelets et al, 2003 ; Lehmann et al, 2005 ; Kikuchi et al, 2007 ; Kindler et al, 2011 ; Nishida et al, 2013 ; Tomescu et al, 2014 ; Sverak et al, 2017 ). However, to date, only two such studies have been done in persons with ASD.…”
Section: Introductionmentioning
confidence: 99%